Estimating the impact of an organised screening programme on cervical cancer incidence: A 26‐year study from northern Italy. Issue 5 (4th December 2018) - Bucchi, Lauro; Baldacchini, Flavia; Mancini, Silvia; Ravaioli, Alessandra; Giuliani, Orietta; Vattiato, Rosa; Falcini, Fabio; Giorgi Rossi, Paolo; Campari, Cinzia; Canuti, Debora; Di Felice, Enza; Sassoli de Bianchi, Priscilla; et al.
Abstract : The impact of the organised cervical cancer (CC) screening programmes implemented in Europe since the 1990s has been insufficiently evaluated. We investigated the changes in CC incidence following the introduction of a screening programme in the Emilia‐Romagna Region (northern Italy). The study period was 1988–2013. The programme, targeting women aged 25–64 years (1, 219, 000 in 2018), started in 1998. The annual incidence rates that would be expected in 1998–2013 in the absence of screening were estimated, first, by analysing the annual rates in 1988–1997 with a log‐linear model and, second, by analysing the annual rates in 1988–2013 with an age‐period model in which the period effect was enforced to be linear. Cervical adenocarcinoma incidence trend over the entire period was used to validate both estimates. Observed annual rates were compared to the two series of expected ones with the incidence rate ratio (IRR). Incidence remained stable during 1988–1997, peaked in 1998 and then decreased until 2007, when it stabilised. The two series of expected rates were virtually coincident and their trends roughly paralleled the stable adenocarcinoma incidence trend. After 2007, the median IRR was 0.60 (95% confidence interval, 0.45–0.81) based on the log‐linear model and 0.58 (95% confidence interval, 0.34–0.97) based on the age‐period model. Thirty‐six to seventy‐five CC cases were prevented annually for an average annual frequency of 6.5 per 100, 000 women in the target population. In summary, consistent circumstantial evidences were obtained that the organised screening programme brought about a 40% reduction in annual CC incidence after 10 years. Abstract : What's new? Evaluations of organized screening programmes for cervical cancer (CC) in Europe remain inadequate. Here the authors report a 40% decrease in annual CC incidence following the introduction of a regional screening programme in 1998. Annual CC incidence rates expected in the absence of screening were robustly determined by two different methods. The programme is now transitioning to screening for human papillomavirus infection.